2021
DOI: 10.1111/ijfs.14970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cucumber pomace fortification on the nutritional, sensorial and technological quality of soft wheat flour‐based noodles

Abstract: The aim of the work was to study the effect of adding cucumber pomace powder (CP) to soft wheat flour used in noodle manufacture. CP is a rich source of minerals and fibres, having high contents of polyphenols and flavonoids were 1.6 mg g −1 GAE and 0.65 mg g −1 QE, respectively, besides its capability to inhibit bacterial and fungal growth and to scavenge DPPH˙(74.44%). The dough rheological properties showed increased extensibility and water absorption but decreased elasticity with adding CP. CP addition sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 69 publications
3
32
1
Order By: Relevance
“…GP raised the protein, lipid, ash and carbohydrate contents of pasta due to their intake of nutrients. Compared to our study, Saad et al [28] showed that cucumber pomace addition in soft wheat noodles increased the mineral and polyphenols content, but decreased protein and carbohydrates. The addition of GP caused higher radical scavenging activity compared to the control, in agreement with the polyphenols content, which presented a raised value for pasta samples with GP.…”
Section: Control and Optimal Product Propertiescontrasting
confidence: 98%
See 3 more Smart Citations
“…GP raised the protein, lipid, ash and carbohydrate contents of pasta due to their intake of nutrients. Compared to our study, Saad et al [28] showed that cucumber pomace addition in soft wheat noodles increased the mineral and polyphenols content, but decreased protein and carbohydrates. The addition of GP caused higher radical scavenging activity compared to the control, in agreement with the polyphenols content, which presented a raised value for pasta samples with GP.…”
Section: Control and Optimal Product Propertiescontrasting
confidence: 98%
“…Acun and Gül [51] also reported raised fiber content of cookies enhanced with seedless grape pomace. Similar to our study, Saad et al [28] showed that the addition of cucumber pomace in soft wheat pasta induced the increase of fibers and polyphenol contents. Fibers are known to have some biological functions, such as activity against cancer, amelioration of gastrointestinal systems functioning, improvement of cardiovascular system activity, and decrease of cholesterol and glycaemia levels in blood [52].…”
Section: Effects Of Grape Peels On Flour Dough and Pasta Qualitysupporting
confidence: 92%
See 2 more Smart Citations
“…The microbial load of raw chicken meat was estimated according to Saad, et al [ 63 ]. The meat filtrate was dissolved in sterilized peptone buffer (1:9 w / v ) in a screw bottle and stirred for 10 min to prepare 10 −1 concentration.…”
Section: Methodsmentioning
confidence: 99%